PEMBINGKAIAN BERITA KONFLIK BERSENJATA NDUGA DI TABLOIDJUBI.COM - Hutahaen, Gita Sere; Lase, Formas Juitan (Interaksi: Jurnal Ilmu Komunikasi, 2021)
The media has an important role as a mediator in conflict events. That role can be realized through the practice of peace journalism. Peace journalism is the ability of the media to bring conflict events toward peace. The conflict that occurred in Nduga, Papua is one of the important events mediated by the media. There are so many people who are disadvantaged if the media such as Tabloidjubi.com does not report the conflict with a peace journalism approach. This article analyzed the reporting of Tabloidjubi.com using the concept of peace journalism and the method of framing analysis on 15 news in the December 2018 edition. This study tried to see whether Tabloidjubi.com uses the perspective of peace journalism in its reporting. The results showed that Tabloidjubi.com had not applied peace journalism adequately. The news still dominates one side as a cause of conflict, namely the warring elites compared to the creation of peace initiatives. So that the role as a mediator in creating resolution, reconstruction and reconciliation has not yet been realized.